How Reading Strategies Affect the Comprehension of Texts in Hypertext Systems. - Madrid-López, Rafael Ignacio; Cañas, José J. (Brill, 2007)
The use of hypertext as a relatively new technology for presenting expository texts has emerged as an alternative to traditional linear prose. One of the main points of hypertext is that it gives the reader easy access to different sources of information on a particular topic. In this context, readers faced with an expository text in hypertext have to develop a particular strategy in order to determine which information they will read and in which order they will access it. However, this possibility introduces new ways of processing information that can affect its comprehension either positively or negatively. In this chapter we revised a series of studies exploring the strategies that readers use when reading a hypertext and how these strategies influence text comprehension. Data reveals that some aspects from navigation behaviour such as the amount of information accessed and the coherence between transited nodes affect comprehension and are modulated by individual differences on cognitive factors.
https://brill.com/page/419324
Keywords: Hipertexto; Lectura - Comprensión; Hypertext comprehension; Reading strategies